Ecological Drivers of Eastern Fox Squirrel Pelage Polymorphism - Potash, Alex D.; Greene, Daniel U.; Mathis, Verity L.; Baiser, Benjamin; Conner, L. Mike; McCleery, Robert A. (Frontiers in Ecology and Evolution, 2020)
The color patterns of an animal’s pelage, feather, or skin serve a variety of adaptive functions; importantly, one function is concealment through background matching. In spatially and temporally heterogeneous environments, some species exhibit multiple distinct color patterns within a population (i.e. color polymorphism). The environmental drivers of color polymorphism are poorly understood. We used the polymorphic eastern fox squirrel (Sciurus niger ssp.; hereafter, fox squirrel) as a model species to investigate the role of environmental factors on pelage coloration. Building upon previous research that investigated the drivers of melanism, we measured fox squirrel pelage coloration across the visible light spectrum. Agouti-colored squirrels were positively associated with increased proportion of burned area in a fox squirrel dispersal buffer. Light-colored (less melanistic) squirrels were positively associated with increasing proportion of cropland in a fox squirrel dispersal buffer. We posit that agouti pelage is broadly adapted to a range of heterogeneous conditions created by fire. Conversely, croplands, once established, are relatively stable ecosystems which promote a consistently adaptive light-colored pelage morph. We suggest that in an increasingly human-dominated environment, spatially and temporally homogeneous processes, such as prescribed burning, may not sufficiently recreate environmental heterogeneity, which could result in lost pelage diversity.